Presidential Threshold Anomaly in Indonesian Government System: Parlementer Reduction in Indonesian Presidential System - Dwi Rianisa Mausili (Bappenas Working Papers, 2019)
The government system running in Indonesia is a combination of presidential systems and parliamentary systems. Based on the 1945 Constitution, Indonesia adheres to a presidential system, but Indonesia, in implementing there are many parts of the parliamentary system that are included in the Indonesian presidential system. The strengthen presidential system effort is still carried out, one of which is the rule of threshold number in Article 222 of Law Number 7 of 2017 about General Elections. However, the presidential threshold (threshold number) is assumed that it will strengthen the presidential system in the Indonesian government system and experience anomalies, irrational and irrelevant. With the presidential threshold, political parties can nominate the presidents and the vice by the provision of the political party or joint political party having 20% of seats or 25% of nationally legitimate votes in the previous legislative elections. With the existence of the presidential threshold, it will give a positive value, namely First, directing political parties to the coalition with other parties. Secondly, political parties after the general election will form two shafts. Those are the bearer axis and the opposition axis. Third, the presidential threshold comes up with a new understanding that is political parties only bearers, so in the 2019 simultaneous elections, there will be elected strong president and vice figures regardless of the small voice of the party that carries them. This paper uses critical discourse analysis toward the opportunities and realization problem challenges of the threshold presidential in Indonesia. The purpose of this writing is the first, how the threshold presidential relevance in Indonesia is, second, how to create an ideal government system thought of the threshold presidential system to reduce parliamentary in the Indonesian presidential system.